Preparatory stage of pedagogical technology for developing ecological competence for master's degree students in management - Khrypunova, Аlina; Gorovyi, Dmytro Anatoliiovych; Vorobiova, Yevheniia (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article develops methodological support for the preparatory stage of pedagogical technology for developing ecological culture for master's degree students in management, which involves supplementing the content of master's degree courses with ecological issues, the development of a special course on ecology and economics, and the adjustment of pre-graduation internship plans and topics for theses and term papers. The objective of the study is to develop and implement ecologically oriented methodological support for the training of master's degree students in management. The subject of the study is the creation of a preparatory stage of pedagogical technology for the formation of ecological competence in master's degree students in management. The purpose of the study is considered in the process of transforming the curriculum based on the development of a preparatory stage of pedagogical technology for the formation of ecological culture in master's degree students in management. The main components of the preparatory stage of pedagogical technology for the formation of ecological culture among master's students in management have been developed.

У статті розроблено методичне забезпечення підготовчого етапу педагогічної технології формування екологічної культури магістрів менеджменту, який передбачає доповнення змісту навчальних дисциплін магістерської підготовки питаннями екологічного характеру, розроблення еколого-економічного спеціального курсу, коригування планів переддипломної практики та тем дипломних і курсових робіт. Також розроблені основні компоненти підготовчого етапу педагогічної технології формування екологічної культури магістрів менеджменту.
Підготовчий етап педагогічної технології формування екологічної компетентності магістрів менеджменту
Keywords: ecological culture; master's students in management; pedagogical technology; preparatory stage; екологічна культура; магістранти менеджменту; педагогічна технологія; підготовчий етап